2017
DOI: 10.5455/apd.268817
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of hippocampus and amygdala volume changes with MRI in patients with social anxiety disorder

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…Similar to Syal et al (2012) and van Tol et al (2010) in younger samples, we found no association between HC volume and SAD. This contrasts with other studies reporting significantly positive associations between SAD and HC volume (Koç et al, 2018; Machado-de-Sousa et al, 2014), and smaller HC volume in patients with SAD (Irle et al, 2010; Liao et al, 2011). These results highlight the need for more research to understand the effect of SAD on the HC and the mechanisms involved, and how these change with age.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similar to Syal et al (2012) and van Tol et al (2010) in younger samples, we found no association between HC volume and SAD. This contrasts with other studies reporting significantly positive associations between SAD and HC volume (Koç et al, 2018; Machado-de-Sousa et al, 2014), and smaller HC volume in patients with SAD (Irle et al, 2010; Liao et al, 2011). These results highlight the need for more research to understand the effect of SAD on the HC and the mechanisms involved, and how these change with age.…”
Section: Discussioncontrasting
confidence: 99%
“…In studies of human patients with anxiety disorders, most studies have focused on PTSD and have found that this condition is associated with reductions in HC volume (Kitayama et al, 2005). In SAD, research has shown hyperactivity in the HC in individuals (Etkin & Wager, 2007) and have found that those with a diagnosis of SAD exhibit larger HC volume compared to controls (Koç et al, 2018; Machado-de-Sousa et al, 2014), while others have observed significantly smaller HC volume compared to controls (Irle et al, 2010; Liao et al, 2011) or no difference in HC volume between individuals with SAD and controls (Syal et al, 2012). One study examining several anxiety disorders also found no HC volume reduction in SAD, GAD or PD patients (van Tol et al, 2010).…”
mentioning
confidence: 99%